The Trauma, Inexplicable: A Psychoanalytic Delve into Louise Erdrich’s The Sentence (International Journal of Food and Nutritional Sciences, 2022)
Even the most trivial thing can have a great impact on life, in both positive andnegative way. Positive effects can always be welcomed as it changes the life of the receiverin a better way. But this is not the same in the case of negative impacts. It can affect themboth physically and mentally